Rare variants in previously identified linkage regions associated with carotid plaque in Dominican Republic families. - Nicole D Dueker; Ashley Beecham; Liyong Wang; Chuanhui Dong; Ralph L Sacco; Susan H Blanton; Tatjana Rundek (PLoS ONE)
Carotid plaque is a subclinical measure of atherosclerosis. We have previously shown measures of carotid plaque to be heritable in a sample of 100 Dominican families and found evidence for linkage and association of common variants (CVs) on 7q36, 11p15, 14q32 and 15q23 with plaque presence. Our current study aimed to refine these regions further and identify rare variants (RVs) influencing plaque presence. Therefore, we performed targeted sequencing of the one LOD unit down region on 7q36, 11p15, 14q32 and 15q23 in 12 Dominican families with evidence for linkage to plaque presence. Gene-based RV analyses were performed using the Sequence Association Test for familial data (F-SKAT) under two filtering algorithms; 1. all exonic RVs and 2. non-synonymous RVs. Replication analyses were performed using a sample of 22 Dominican families and 556 unrelated Dominicans with Exome Array data. To identify additional non-synonymous RVs influencing plaque, we looked for co-segregation of RVs with plaque in each of the sequenced families. Our most strongly associated gene with evidence for replication was AMPD3 which showed suggestive association with plaque presence in the sequenced families (exonic RV p = 0.003, nonsynonymous RV p = 0.005) and replication families (exonic RV p = 0.04, nonsynonymous RV p = 0.02). Examination of the sequenced family pedigrees revealed two missense variants on chromosome 11 which co-segregated with plaque presence in one of our families; rs61751342 (located in DENND2B), and rs61760882 (located in RNF141). The rs61751342 missense variant is an eQTL for SCUBE2 in the atrial appendage. Notably, SCUBE2 encodes a protein which interacts with vascular endothelial growth factor (VEGF) receptor 2 to regulate VEGF-induced angiogenesis, thus providing biologic plausibility for this gene in atherosclerosis. In conclusion, using targeted sequencing of previously-identified linkage regions, we have identified suggestive evidence for the role of RVs in carotid plaque pathogenesis.